Electrophilic Compounds in the Human Diet and Their Role in the Induction of the Transcription Factor NRF2 - Andrés, Celia María Curieses; Pérez de la Lastra, José Manuel; Bustamante Munguira, Elena; Juan, Celia Andrés; Plou, Francisco J.; Pérez Lebeña, Eduardo (International journal of molecular sciences, 2024)
The phrase “Let food be thy medicine…” means that food can be a form of medicine and medicine can be a form of food; in other words, that the diet we eat can have a significant impact on our health and well-being. Today, this phrase is gaining prominence as more and more scientific evidence suggests that one’s diet can help prevent and treat disease. A diet rich in fruits, vegetables, whole grains, and lean protein can help reduce the risk of heart disease, cancer, diabetes, and other health problems and, on the other hand, a diet rich in processed foods, added sugars, and saturated fats can increase the risk of the same diseases. Electrophilic compounds in the diet can have a significant impact on our health, and they are molecules that covalently modify cysteine residues present in the thiol-rich Keap1 protein. These compounds bind to Keap1 and activate NRF2, which promotes its translocation to the nucleus and its binding to DNA in the ARE region, triggering the antioxidant response and protecting against oxidative stress. These compounds include polyphenols and flavonoids that are nucleophilic but are converted to electrophilic quinones by metabolic enzymes such as polyphenol oxidases (PPOs) and sulfur compounds present in foods such as the Brassica genus (broccoli, cauliflower, cabbage, Brussel sprouts, etc.) and garlic. This review summarizes our current knowledge on this subject.